Depot‐ and gender‐specific expression of NLRP3 inflammasome and toll‐like receptors in adipose tissue of cancer patients. (18th April 2016) - Shimabukuro, Michio; Sato, Hiromi; Izaki, Hirofumi; Fukuda, Daiju; Uematsu, Etsuko; Hirata, Yoichiro; Yagi, Shusuke; Soeki, Takeshi; Sakaue, Hiroshi; Kanayama, Hiro‐omi; Masuzaki, Hiroaki; Sata, Masataka
Abstract: Gender difference in obesity‐associated cardiovascular complication could be derived from divergent chronic inflammation. We evaluated depot‐ and gender‐specific regulation of the innate immune system in human adipose tissues. Pair samples were obtained from subcutaneous (SAT) and visceral adipose tissue (VAT) during elective surgery (Male: 35; Female: 27). Expressions of pro‐ and anti‐inflammatory adipocytokines were evaluated by semi‐quantitative qPCR. Adipose cell‐size distribution was obtained from tissue samples fixed in osmium tetroxide and analyzed by Beckman Coulter Multisizer. Levels of adiponectin were higher in SAT and VAT of female than those of male ( P < 0.001 and P = 0.011, respectively). NLRP3, IL1β‐IL18, TLR2 were comparable in SAT and VAT between genders. However, TLR4 and TLR9 were increased in female SAT and VAT and HMGB1 in female VAT. Levels of adiponectin were not correlated with mean diameter of adipocyte ( φ, μm) in SAT and VAT of male, but negatively well correlated in those of female ( r = −0.392 and r = −0.616). Such negative correlations were also observed between levels of TLR2, TLR4, and HMGB1 and φ in female. Levels of NLRP3 and IL1β were positively correlated with φ in male, but not in female. In conclusion, Innate signals were differentially expressed in male and female adipose tissues, suggesting that the depot‐ and gender‐specific signals could be related to gender difference in chronic inflammation. © 2016 BioFactors, 42(4):397–406, 2016